Understanding employee burnout: The interplay between workload and non-physical work environment - Raja, I Gusti Made Saka; Nastiti, Rizky; Akbar, Masithah (Institute of Computer Science (IOCS), 2026)
Employee burnout has become a critical issue in organizational settings, particularly in companies facing increasing job demands and dynamic work environments. This study aims to examine the effect of workload and non-physical work environment on employee burnout at PT Kalimas Kharisma Banjarmasin, both partially and simultaneously. Employing a quantitative research approach, primary data were collected through structured questionnaires distributed to 82 employees selected using the Slovin formula. The data were analyzed using statistical techniques with SPSS software. The results indicate that workload has a positive and significant effect on employee burnout, suggesting that excessive or poorly managed workloads contribute substantially to physical and emotional exhaustion. In contrast, the non-physical work environment shows a negative but statistically insignificant effect on burnout, indicating that although psychosocial aspects such as interpersonal relationships and communication may help reduce burnout, their independent influence is relatively weak. Simultaneously, workload and non-physical work environment have a significant effect on employee burnout. These findings imply that effective workload management is essential to mitigate burnout, while efforts to foster a supportive, safe, and comfortable non-physical work environment can strengthen relationships between supervisors and subordinates and enhance overall employee well-being.